CT- and MRI-based volumetry for Chiari-like malformation and syringomyelia in Pomeranians - Santifort, Koen M.; Carrera, Ines; Mandigers, Paul J. J. (Frontiers in Veterinary Science, 2025)
IntroductionVolumetric studies in relation to CM/SM have not been reported in Pomeranians. In this study, we aim to (1) report the intermodality agreement between CT- and MRI-based volumetric measurements of the skull and cervical spinal canal, and (2) assess for differences and associations between the volumetric measurements and CM/SM status.MethodsPomeranians were included that underwent CT and MRI studies during the period of February 2022–June 2024. Frontal sinus volume (FSV), caudal cranial fossa volume (CCFV), rostral and middle cranial fossa volume (RMCFV), caudal cranial fossa parenchymal volume (CCFPV), rostral and middle cranial fossa parenchymal volume (RMCFPV), cerebellar parenchymal volume (CPV), brain stem parenchymal volume (BSPV), ventricular system volume (VSV), and spinal canal volume between C1-C7 (CSCV) were measured. CCFV to RMCFV volume index (VI) and CCFPV to CCFV (CCFPV%) were calculated. Agreement between MRI- and CT-based quantitative measurements was assessed with intraclass correlation coefficients. Inferential statistical tests including logistic regression modeling were performed to assess for associations between variables and CM/SM status.ResultsFor all volumetric assessments that were performed on both CT and MRI, agreement was good or excellent. There were significant differences between SM normal and abnormal dogs for body weight as well as all volumetric parameters except for CCFPV% and RMCFV. Multiple logistic regression showed that a smaller CCFV and larger VSV were associated with SM.ConclusionSmaller CCFV and larger VSV are associated with the development of SM in Pomeranians and have increased odds of SM.